2006
DOI: 10.1038/sj.ki.5000019
|View full text |Cite
|
Sign up to set email alerts
|

Length polymorphism in heme oxygenase-1 is associated with arteriovenous fistula patency in hemodialysis patients

Abstract: Heme oxygenase-1 (HO-1) is a rate-limiting enzyme in heme degradation, producing carbon monoxide (CO), which carries potent antiproliferative and anti-inflammatory effects in the vascular walls. Transcription of the HO-1 gene is regulated by the length polymorphism of dinucleotide guanosine thymine repeat (GT)(n) in the promoter region, which was measured in this study to determine its association with arteriovenous fistula (AVF) failure in Chinese hemodialysis (HD) patients in Taiwan. L allele means (GT)(n)>o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 39 publications
1
67
0
Order By: Relevance
“…We suggest that these findings may offer insights into the recent observation that polymorphisms in the HO-1 gene, characterized by long GT repeats, may increase the risk for recurrent venous thrombosis 20 and for dysfunction of arteriovenous fistulas the latter caused, in part, by thrombosis occurring in the venous limbs of these fistulas. 49 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suggest that these findings may offer insights into the recent observation that polymorphisms in the HO-1 gene, characterized by long GT repeats, may increase the risk for recurrent venous thrombosis 20 and for dysfunction of arteriovenous fistulas the latter caused, in part, by thrombosis occurring in the venous limbs of these fistulas. 49 …”
Section: Discussionmentioning
confidence: 99%
“…29 Interestingly, dysfunction and failure of arteriovenous fistulas are more likely to occur in patients exhibiting polymorphisms in the HO-1 gene characterized by long GT repeats. 49 Long GT repeats in the HO-1 promoter, as shown by others, may lead to reduced expression or inducibility of HO-1. [17][18][19] We suggest that the exaggerated inflammatory response and the markedly impaired resolution of venous clot, as observed in the present study, may be germane to the premature cessation of blood flow that we recently observed in arteriovenous fistulas created in HO-1 deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…Such omissions are not confined to the anaesthetic literature. Studying polymorphisms for genes that code for the enzyme heme-oxygenase-1 as a risk factor for arteriovenous fistula impotency in patients with renal failure, Lin et al [26] were criticised for their oversight in not reporting adherence of their measured alleles to Hardy's Law [27]. Indeed, general guidance issued on the proper conduct and reporting of genotype-phenotype association studies confirms Hardy's Law as an essential step in the quality control process [28].…”
Section: Relevance For Clinical Anaesthesiamentioning
confidence: 99%
“…Moreover, HO-1 may also have intrinsic protective properties against inflammation, oxidant stress, and vascular proliferation. In a seminal clinical study, Lin et al demonstrated that patients with gene polymorphisms of HO-1 characterized by long GT repeats (less production of HO-1) were more likely to have worse AVF patency (25). A subsequent experimental study published by Juncos et al in a murine model of AVF, where the HO-1 gene was knocked out, evaluated the functional and biologic significance of HO-1 in AVF development (26).…”
Section: Experimental Models Exploring Downstream Vascular Biology Anmentioning
confidence: 99%